The rutting resistance and resilient moduli of Pre-Vulcanized Liquid Natural Rubber modified asphaltic concrete in warm-mix temperature condition - Irfan,; Subagio, Bambang Sugeng; Hariyadi, Eri Susanto; Maha, Indra (Journal of Civil Engineering and Management, 2022)
Pre-Vulcanized Liquid Natural Rubber (PVLNR) modified asphalt leaves problems such as increasing the viscosity, thereby increasing the mixing and compaction temperature up to 175 °C, accelerating the ageing process. Therefore it is necessary to do developing methods using PVLNR at lower mixing temperatures requires warm-mix technology. This study aimed to evaluate the use of PVLNR modified asphalt in warm mix asphalt (WMA). Laboratory testing includes rheological modified asphalt, the workability analysis, Resilient Modulus and Deformation. The results showed that the PVLNR content decreased penetration increased the softening point and asphalt viscosity. In addition, additive Rediset LQ plays a role in reducing asphalt viscosity. The advantages of PVLNR modified asphalt are increasing elastic recovery, saving asphalt consumption and increasing the Modulus of hot mix asphalt rubber (HAR) and warm mix asphalt rubber (WAR). In addition, the Rutting resistance of WAR is better than that of HMA and WMA.